The Perspectives on physical education teachers: are sporting skills more important than teaching skills? A systematic literature review - Hendya Alif Junanda; Ferry Fendrian; Indra Sholehudin (Journal of Physical and Outdoor Education, 2026)
Physical Education teachers are often assessed on their ability to perform and demonstrate sporting skills. This perspective raises a fundamental question as to whether sporting skills are more important than teaching ability in determining the quality of a Physical Education teacher. This study aims to systematically analyse the scientific literature on the role of sporting skills, teaching ability, and pedagogical content knowledge in the professionalism of Physical Education teachers. This study employed a Systematic Literature Review method in accordance with the PRISMA 2020 guidelines. The literature search was conducted in the Scopus database using keywords related to physical education teachers, sporting skills, content knowledge, pedagogical content knowledge, teaching competence, teacher support, and student perception. The initial search resulted in 428 articles; following the selection process, 32 articles met the criteria for the literature review and were analysed using a narrative-thematic approach. The findings indicate that sporting skills are crucial for physical education teachers as they are linked to content mastery. However, sporting skills alone are not sufficient to ensure meaningful learning. Teaching ability and pedagogical content knowledge play a central role in transforming sporting skills into learning experiences that are safe, inclusive, enjoyable and meaningful for pupils. This study found that sporting skills are important, but no more important than teaching ability. Experienced physical education teachers are those who can combine sporting skills, pedagogical expertise and sensitivity to the diversity of their pupils.